Evaluation of brown adipose tissue with intermolecular double‐quantum coherence magnetic resonance spectroscopy at 3.0 T. (18th January 2022) - Lin, Liangjie; Zhang, Qinhe; Wang, Nan; Jiang, Ke; Lin, Yanqin; Chen, Zhong; Song, Qingwei; Liu, Ailian; Wang, Jiazheng
Abstract : In the current study, we propose a single‐voxel (SV) magnetic resonance spectroscopy (MRS) pulse sequence, based on intermolecular double‐quantum coherence (iDQC), for in vivo specific assessment of brown adipose tissue (BAT) at 3 T. The multilocular adipocyte, present in BAT, typically contains a large number of small lipid droplets surrounded by abundant intracellular water, while the monolocular adipocyte, present in white adipose tissue (WAT), accommodates only a single large lipid droplet with much less water content. The SV‐iDQC sequence probes the spatial correlation between water and fat spins at a distance of about the size of an adipocyte, thus can be used for assessment of BAT, even when mixed with WAT and/or muscle tissues. This sequence for measurement of water‐to‐fat (water‐fat) iDQC signals was tested on phantoms and mouse BAT and WAT tissues. It was then used to differentiate adipose tissues in the supraclavicular and subcutaneous regions of healthy youth human volunteers (n = 6). Phantom results with water‐fat emulsions demonstrated enhanced water‐fat iDQC signal with increased voxel size, increased energy level of emulsification, or increased distribution balance of water and fat spins. The animal tissue experiments resulted in obvious water‐fat iDQC signal in mouse BAT, while this signal was almost absent in the WAT spectrum. The optimal choice of the dipolar coupling distance for the observation was approximately 100 μm, as tested on both emulsion phantom and animal tissue. The water‐fat iDQC signals observed in the supraclavicular adipose tissues were higher than in the subcutaneous adipose tissues in healthy young volunteers (0.43 ± 0.36 vs. 0.10 ± 0.06, p = 0.06). It was concluded that the iDQC‐based sequence has potential for assessment of mouse and human BAT at 3 T, which is of interest for clinical research and the diagnosis of obesity and associated diseases. Abstract : We propose a single‐voxel, magnetic resonance spectroscopy (MRS) pulse sequence, based on intermolecular double‐quantum coherence (iDQC), for the clinical assessment of brown adipose tissue (BAT) at 3 T. The technique efficiency was evidenced by phantom experiments, by animal models, and by in vivo studies on the supraclavicular and subcutaneous adipose tissues in healthy young volunteers.